The impact of individual differences in weather sensitivity on weather-related purchase intentions. (January 2018) - Moon, Sangkil; Kwon, JaeHwan; Jung, Sang-Uk; Bae, Young Han
Marketing scholars have demonstrated the impacts of weather on consumer behavior at the aggregate level; however, they have not fully analyzed how individual differences in weather sensitivity (WS) play a role in consumers' purchase decisions. Therefore, we examine how individual differences in WS influence weather-related purchases (e.g., flood insurance, buying hot coffee on a cold, rainy day). Specifically, we find that consumers who are high in WS tend to respond to such weather-related purchases more positively. Furthermore, we identify prosocial behavior as a factor that positively impacts these purchases, given that people who are high in prosocial behavior tend to be more responsive to the general environment, including the weather. We also indicate hedonic consumption as another positive factor, in that hedonic consumption can stimulate a positive weather effect (e.g., I want to enjoy shopping today because the weather is so nice). Using successive preliminary and main surveys, we test these hypotheses and confirm the results empirically. From a managerial perspective, marketers can develop differential marketing segmentation strategies between more and less weather-sensitive consumers by using our findings.